High‐Strain Peano‐HASEL Actuators. (15th December 2019) - Wang, Xingrui; Mitchell, Shane K.; Rumley, Ellen H.; Rothemund, Philipp; Keplinger, Christoph
Abstract: Soft robots are intrinsically safe for use near humans and adaptable when operated in unstructured environments, thereby offering capabilities beyond traditional robots based on rigid components. Soft actuators are key components of soft robots; recently developed hydraulically amplified self‐healing electrostatic (HASEL) actuators provide a versatile framework to create high‐speed actuators with excellent all‐around performance. Peano‐HASEL actuators linearly contract upon application of voltage, closely mimicking the behavior of muscle. Peano‐HASEL actuators, however, produce a maximum strain of ≈15%, while skeletal muscles achieve ≈20% on average. Here, a new type of HASEL is introduced, termed high‐strain Peano‐HASEL (HS‐Peano‐HASEL) actuator, that achieves linear contraction up to ≈24%. A wide range of performance metrics are investigated, and the maximum strain of multiunit HS‐Peano‐HASEL actuators is optimized by varying materials and geometry. Furthermore, an artificial circular muscle (ACM) based on the HS‐Peano‐HASEL acts as a tubular pump, resembling the primordial heart of an ascidian. Additionally, a strain‐amplifying pulley system is introduced to increase the maximum strain of an HS‐Peano‐HASEL to 42%. The muscle‐like maximum actuation strain and excellent demonstrated all‐around performance of HS‐Peano‐HASEL actuators make them promising candidates for use in artificial organs, life‐like robotic faces, and a variety of other robotic systems. Abstract : High‐strain Peano hydraulically amplified self‐healing electrostatic (HASEL) actuators are electrohydraulically driven artificial muscles that feature high‐speed linear contraction of ≈24%, matching average values for skeletal muscles. The materials and geometry are optimized, and the application as a soft pump is demonstrated; other potential uses include bioinspired robots, robotic faces, and artificial organs.